A Purinergic Trail for Metastases. (March 2017) - Ferrari, Davide; Malavasi, Fabio; Antonioli, Luca
Abstract : Nucleotides and nucleosides have emerged as important modulators of tumor biology. Recently acquired evidence shows that, when these molecules are released by cancer cells or surrounding tissues, they act as potent prometastatic factors, favoring tumor cell migration and tissue colonization. Therefore, nucleotides and nucleosides should be considered as a new class of prometastatic factors. In this review, we focus on the prometastatic roles of nucleotides and discuss future applications of purinergic signaling modulation in view of antimetastatic therapies. Trends: Release of nucleotides and nucleosides in the extracellular milieu has been demonstrated in many tissues. Once released extracellularly, they have multiple functions by binding to specific cell membrane purinergic receptors. The ectonucleotidases CD39 and CD73 are plasma membrane enzymes converting extracellular ATP/ADP to AMP and AMP to adenosine, respectively. Therefore, their enzymatic activity is fundamental in determining availability of P2 and P1 receptor agonists and the global outcome of purinergic response. Overexpression of P1 or P2 receptor subtypes by cancer cells can support cancer growth and invasiveness while decreasing efficacy of the immune surveillance.